Awareness, attitude, and practice of dental practitioners toward management of endodontically treated teeth and factors associated with it: A questionnaire descriptive survey - Deepak Sharma; Sneh Agrawal; Parag Gangurde; Sumeet Agarwal; Reema Srichand; Vivek Sharma (Journal of Family Medicine and Primary Care, 2020)
Background: Endodontically treated teeth should be prosthodontically managed properly to add life to the teeth, and hence the main aim of this study was to explore awareness, attitude, and practice of dental practitioners toward management of endodontically treated teeth and factors associated with it. Materials and Methods: It was a cross-sectional, descriptive questionnaire study conducted among dental practitioners working in private clinics. The study was conducted in August 2019. The survey was conducted among 239 participants. In this study, a close-ended interview schedule was prepared for perception and practice of dental specialists. Results: Most of the dental professionals (31.79%) preferred full coverage crown for restoring the grossly decayed endodontically treated teeth. Awareness regarding prosthodontic management of endodontically treated teeth was better among specialists (13.75%) than bachelor's degree holders. Attitude was neutral among most of the study participants (46.86%) and practice scores toward prosthodontic management of endodontically treated teeth was good. Gender and degree were significantly associated (P = 0.02*) (P = 0.05*), (P = 0.00***) (P = 0.05*) with awareness and practice of study participants. Conclusion: A majority of study subjects in this study had moderate awareness, neutral attitude, and good practice regarding restoration of endodontically treated teeth.